Aneurysm of the Common Iliac Artery Revealing a Behcet's Disease - Elqatni, M.; Fatihi, J.; Elomri, N.; Jira, M.; Sekkach, Y.; Amezyane, T.; Ennibi, K.; Abouzahir, A. (Journal of Hypertension and Cardiology, 2020)
A case report of a common iliac artery aneurysm revealing underlying Behçet’s disease. It reviews diagnostic clues, vascular complications, and multidisciplinary management.
Keywords: hypertension; hypertension prevalence; systolic blood pressure (SBP); diastolic blood pressure (DBP); sodium intake; Jiangxi